IMPLEMENTASI KNOWLEDGE MANAGEMENT MELALUI PERPUSTAKAAN KHUSUS DI INSTANSI PEMERINTAH - Khairunisa Fathonah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the role of special libraries in supporting the implementation of Knowledge Management (KM) in government institutions and to examine the strategies, challenges, and impacts on organizational performance improvement. The research employed a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and document analysis. Data sources consisted of primary data obtained from informants involved in knowledge management practices and secondary data derived from policy documents, organizational reports, and relevant scholarly literature. Data were analyzed using an interactive model through the stages of data reduction, data display, and conclusion drawing, supported by source and method triangulation to ensure validity. The findings indicate that special libraries function as knowledge centers that manage explicit knowledge, facilitate the conversion of tacit knowledge, and support information access through the utilization of technology such as institutional repositories, digital libraries, and knowledge portals. The implementation of Knowledge Management through special libraries contributes to improved work efficiency, better decision-making quality, enhanced public service innovation, and improved service delivery to the community. However, the implementation still faces several challenges, including organizational cultures that do not fully support knowledge sharing, limited human resource competencies, and inadequate technological infrastructure. The novelty of this study lies in strengthening the role of special libraries as strategic Knowledge Management infrastructure based on the integration of people, process, and technology within the public sector context. The implications for the field of education include providing conceptual contributions to the development of libraries as organizational learning centers and serving as a reference for future research on knowledge management and the development of special libraries in the era of digital transformation.